Efektivitas Perencanaan Pembelajaran Pendidikan Agama Islam Dalam Meningkatkan Kualitas Pembelajaran di SMP IT Al-Husna Lebong - Rana Meiyanda; Mutiara Mahardika; Wahyu Asbabul Jannah; Kusen; Karliana Indrawari (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the effectiveness of Islamic Religious Education learning planning at SMP IT Al-Husna Lebong. The study employed a qualitative approach with a descriptive analytical research design to obtain an in-depth understanding of the preparation and implementation of Lesson Plans (Rencana Pelaksanaan Pembelajaran / RPP) in the learning process. The data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers as the research subjects. The data were analyzed using data reduction, data display, and conclusion drawing techniques through descriptive qualitative analysis. The findings revealed that the teachers had prepared lesson plans in accordance with the required learning components, including learning objectives, materials, methods, learning activities, and evaluation. The implementation of lesson plans helped teachers conduct learning activities in a more systematic, effective, and directed manner. Teachers also applied various learning methods, such as lectures, discussions, group work, and assignments to enhance students’ participation in the learning process. However, the study also found several obstacles, including limited learning facilities, lack of mastery of innovative learning methods, and the tendency to use lesson plans merely as administrative requirements without optimal implementation. This study contributes theoretically to the development of studies on the effectiveness of learning planning in Islamic Religious Education and practically provides insights for teachers and educational institutions to improve the quality of lesson plan preparation and implementation.